The Development of the Consulship in the Early Republic: Evidence for an Alternative Version in Livy - Koptev, Aleksandr (2018)
The traditional version of the establishment of the consulship in 509 BC and its restoration in 449 and 367 BC was a product of a long period of historiographical development. A great problem is inconsistencies in early republican chronology due to later annalistic historians combining earlier versions. In pre-Fabian oral tradition, it was the capture of Veii that inspired the creation of a new legion with its own praetor to protect new Roman tribes on the Etruscan bank of the Tiber. Early Roman historiography shaped two possible versions of the establishment of the (patrician) consulship after the Veientine war, dating it to 483–474 and 406–396 BC. According to one version, the original title of the early magistracy was changed from ‘praetor’ to ‘consul’ in 449 BC. The other version synchronised the restoration of the consulship with the admission of the plebeians to this magistracy in 367 BC. The Gallic Sack of 387 BC was followed with the creation of the garrison service in Rome, the milites seniorum, whos commander was the praetor urbanus. An analysis of Livy’s account in Books VI, VII, and VIII shows that the plebeians, who received one consular office in 367 BC and were admitted to the praetorship in 342 BC, were mostly members of those communities that were given Roman citizenship after the abolition of the Latin League.
Keywords: Rome Republic; Livy